Deep Reinforcement Learning for the Card Game Dominion - Kolomazník, Vojtěch; Zamazal, Ondřej; Máša, Petr; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis aims to propose an approach using deep reinforcement learning (deep RL) for the card game Dominion. Existing deep RL approaches are studied and compared, so that a deep RL agent can be implemented. After that, the thesis attempts to determine whether a properly trained agent can perform above the level of a simple heuristic, find out which adjustments allow the agent to perform better in a partially observable environment and study the choices made by the agent. Dominion is a deck-building card game, which presents many challenges to the RL community. It violates the Markov property because the state is not fully observable to the agent. Moreover, there is inherent stochasticity because the agent’s deck gets shuffled between turns. Current academic research has attempted to apply deep Q-networks and policy gradients to solve the game with varying success. One of the biggest unanswered questions relates to the calculation of the rewards. Both Monte Carlo and temporal-difference methods yield sufficient performance in different scenarios. For the purpose of this thesis, several modifications were added to decrease the complexity of the problem. The selection of cards used in the game was frozen between games and the action phase of an agent’s turn was handled with a heuristic. Only the buying phase was controlled directly by the agent. For this thesis, REINFORCE method relying on policy gradients and Monte Carlo returns displayed superior performance compared to deep Q-networks and actor-critic architectures using temporal-difference returns. It obtained a 95 percent win rate against Big Money heuristic and an 88 percent win rate against Smithy heuristic after only 20 thousand simulated games.
Vedoucí práce: Ondřej Zamazal
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: data analytics [obor bakal. práce]; bakalářské práce; bachelor's theses